Performance of Retaining Walls with Compressible Inclusions under Seismic Loading - Dram, Abdelkader; Benmebarek, Sadok; Balunaini, Umashankar (Civil Engineering Journal, 2020)
This paper investigates the possible application of recycled tyre shreds as compressible inclusion behind retaining walls under dynamic loading. It is a novel method to reduce the magnitude of earthquake-induced dynamic forces against rigid earth retaining wall structures. A numerical model to analyze the behavior of retaining walls with compressible cushion was developed in PLAXIS 2D, a two-dimensional finite element analysis based software, and the results were validated by comparison with experimental findings from physical models. The study evaluates the effects of thickness of compressible cushion and the friction angle of the backfill on the seismic performance of retaining walls. To assess the effect of frequency on wall performance with and without cushion, the wall was subjected to 15 cycles of sinusoidal excitation with acceleration amplitudes of 0.1g to 0.3g at a frequency of 7 Hz. The results from the numerical analysis indicate that the permanent displacements of the wall were reduced in the range of 38% to 52% and the horizontal earth pressures were reduced by about 55% to 76% due to the presence of tyre shreds as a compressible cushion between the wall and backfill. Results showed that the dynamic load against the retaining wall can be considerably reduced through the proposed technique.Â Doi: 10.28991/cej-2020-03091631 Full Text: PDF